Decision-making in task-oriented and interaction-oriented groups - Schach, Liane (Department of Psychology, 2016)
Within an organisation, leadership involves accomplishing goals by working with and through people. This comprises the concepts of concern for the task and concern for relationships, and leadership research has been concerned with predicting the way in which these concepts interact, whether they are independent dimensions or not and how a balance may be achieved between the two. The present research follows directly on from the Ohio State Leadership studies (Fleishman and Peters, 1962) which viewed the concepts of task-orientation (Initiating Structure) and relationship-orientation (Consideration) as two separate dimensions and not as situated along a single continuum. Research following on from this (e.g. Blake and Mouton, 1964; and Hersey and Blanchard, 1969) all take this concept of these two dimensions as their starting point.